Prevalence and associated factors of undiagnosed glycaemic disorders in men with erectile dysfunction attending a primary care clinic - Ng, YL; Teoh, SH; Syahnaz, MH; Mohd Radzniwan A Rashid (Elsevier Science BV, 2024)
Indexed by WOS/SCOPUS